PENATALAKSANAAN HOLISTIK PADA PASIEN WANITA PENJUAL JAJANAN PASAR USIA 67 TAHUN DENGAN GOUT ARTHRITIS MELALUI PENDEKATAN KEODKTERAN KELUARGA - Maharani, Raihan Syifa; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2024)
Gout arthritis is a progressive chronic inflammatory disease due to deposition of monosodium urate (MSU) crystals in the joints due to long-lasting hyperuricemia with several associated risk factors including excessive consumption of purine compounds and lack of physical activity. Gout arthritis needs to be managed comprehensively and holistically through the role of the family doctor in order to improve the patient's quality of life and prevent complications that can occur. Apply the principles of family medicine services to patients based on the problems found and carry out holistic and comprehensive management using the principles of patient-centered and family approach based on Evidence Based Medicine. This study is a case report. Primary data were obtained from anamnesis, physical examination, and home visits to assess the physical environment. Secondary data was obtained from the patient's medical record. Assessment based on holistic diagnostics at the beginning, process, and end of the study. Mrs. M, 67 years old, came with complaints of joint pain in both knees since 1 week ago. The patient was diagnosed with gout arthritis. In this case, diagnosis and treatment have been carried out according to the theory and related journals. Management has been carried out with the approach of family doctor Ny. M 67 years old with Gout arthritis adjusted based on initial holistic diagnostics. The interventions carried out have increased patient knowledge and improved the healthy lifestyle of patients and their families as indicated by improvements in the final holistic diagnostic.